ANALISIS KESULITAN SISWA DALAM PEMECAHAN MASALAH MATEMATIK SISWA KELAS X SMK BINA INSAN BANGSA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN - Nurhayati Nurhayati; Martin Bernard (Journal on Education, 2019)
This article is an analysis of the results of problem solving questions of class X students of Bina Insan Bangsa Vocational School. The analysis was conducted to find out the problems experienced by students and to determine the level of problem-solving difficulties of students of the National Vocational High School. The research method used is descriptive qualitative. The samples taken for this study were 20 class X students of Bina Insan Bangsa Vocational School. The mathematical problem solving test instruments provided were 3 items. The results of the analysis obtained based on the written test carried out is that the mathematical problem solving of students at the National Human Resources Vocational School is relatively low.